Integrated lighting system for an office space in the tropics of Costa Rica - Ávila-Zamora, Andrea (2023)
Today, thanks to advances in research and technological development, natural and artificial light is concerned with the visual well-being of man and the search for the ideal lighting conditions, which guarantee optimal development in their daily tasks. Through the descriptive methodology, it was proposed that despite the advances and continuous efforts to innovate in technology that refers to the control and redirection of natural lighting, there are still paths to explore, since in many cases, These advances have guaranteed great savings in energy consumption but not in the visual satisfaction of its users. Hypotheses were formulated in the search for the use of different control devices and redirection of sunlight inside office spaces, which allows office users to control glare, which is the main problem present in the climate tropical. This research concluded that although explorations have already been carried out on the subject, a theoretical-experimental work would represent one more contribution to the daily task of research to improve knowledge about the control of natural lighting in tropical climate countries.